THE PHENOMENOLOGY OF CORETAX IMPLEMENTATION UNDER TWO FINANCE MINISTERS: TAXPAYER EXPERIENCES - Bernard Sirait; Agus Ismaya Hasanudin; Roza Mulyadi (Jurnal Interprof, 2026)
Purpose: This study explores the phenomenon of Core Tax Administration System (Coretax) implementation under two Indonesian finance ministers by examining taxpayers' perceptions, challenges, and responses. Research Methodology: A descriptive phenomenological approach was used at the Banten Regional Office of the Directorate General of Taxes. Data were gathered through in-depth semi-structured interviews, participatory observation, documentation, and member checking involving 12 corporate taxpayers with Taxable Entrepreneur status and one tax counselor. Data analysis used intentionality analysis, epoche or bracketing, noema-noesis interpretation, and eidetic reduction. Results: Taxpayers perceived Coretax as a necessary modernization that integrates tax services and can improve efficiency. Nevertheless, early implementation was marked by system errors, slow access, login failures, limited digital literacy, insufficient initial socialization, and data-security concerns. The later period showed perceived improvements in stability, communication, and assistance, although technical problems persisted during peak reporting periods. Conclusions: Coretax adoption depends not only on technological readiness but also on user experience, institutional responsiveness, communication, and continuity of digital tax reform. Limitations: The findings are limited to early implementation experiences of corporate taxpayers within Banten and therefore should not be generalized to all taxpayer segments. Contributions: This study contributes to digital tax administration literature by integrating phenomenology with TAM, UX, UTAUT, and public-sector reform perspectives.